The Role of Dendritic Cell Maturation in the Induction of Insulin-Dependent Diabetes Mellitus - Mbongue, Jacques C.; Nieves, Hector A.; Torrez, Timothy W.; Langridge, William H. R. (Frontiers in Immunology, 2017)
Dendritic cells (DCs) are considered the dominant antigen presenting cells (APC) in humans and are largely responsible for initiation and guidance of innate and adaptive immune responses involved in maintenance of immunological homeostasis. Immature dendritic cells (iDCs), phagocytize pathogens and toxic proteins and degrade them into small fragments in endosomal vesicles for presentation to naïve cognate T cells (Th0). In addition to stimulation of immunity, DCs are responsible for the induction and maintenance of immune tolerance towards self-antigens. Dendritic cell maturation is initiated when they cease taking up antigens and with the help of several chemokines migrate from the periphery to adjacent lymph nodes or the spleen where during continued maturation they present stored antigens on surface MHCII receptor molecules to the T cell receptor (Tcr) of cognate naive T helper (Th0) cells. During antigen presentation, the DCs upregulate co-stimulatory factor CD86, CD80, CD83, and CD40 molecule biosynthesis on their plasma membrane. The activated DC CD86 and CD80 costimulatory factor molecules bind cognate CD28 receptors on the Th0 cell membrane and secrete pro-inflammatory (IL-12) or anti-inflammatory (IL-10) cytokines that direct T cell differentiation and proliferation into pro- or anti-inflammatory T cell subsets. However, the details of this process remain incomplete. In this review we describe the process of DC maturation in detail and what is known concerning the role of DC maturation in the onset and prevention of Type 1 diabetes tissue specific autoimmunity.